Smart Gloves for Women with IoT Technology - Dr. T. Nedunchezhian, Dr.S.Jayalakshmi, A. Lakshmi Parvathi, P.Anitha, B.Sudhakar (Mathematical Statistician and Engineering Applications, 2023)
In excess of 81% of ladies in the populace, as per a GFK review, have encountered some type of provocation eventually in their lives. This measurement delineates the degree of difficulties ladies face in fostering their certainty, developing, and advancing in a general public that is unendingly tormented by the possibility of a perilous climate, It has upset their capacity to prosper and denied females freedom and similar privileges as men. They are allowed to put themselves out there whenever they need without stressing over their security or general prosperity or whether they need a chaperone to deal with their outward way of behaving. We made an IoT-based gadget while considering these potential outcomes to resolve this cultural issue. the first The reason for this gadget is to give ladies a device so they might have a good sense of reassurance and secure while out in broad daylight at any odd hour, without feeling vulnerable and fearful. This gadget’s different parts incorporate a crisis button, GPS, GSM, a LCD, and an Arduino UNO. We have an implicit report the self-preservation system for ladies’ security to help them in some most pessimistic scenario situations, for example, attack and badgering as well as the potential for being captured by drivers in the road, on open transportation, and in taxis. Ladies are driving and making critical commitments in various ventures, including business, training, and the wellbeing area, to give some examples, however there might have been a lot more ladies working in these positions. The badgering and wellbeing worries that deny them of their justified situations in the public eye are not new to mankind. Ladies will not need to stress over their security in open any more in the event that they use this gadget.